Clases virtuales y su influencia en el aprendizaje de los estudiantes de 4to año de EGB de la Escuela Lucila Godoy, San Luis de Zapotal. Ventanas 2022 - Cervonet Rosario, Sebastian Ronald (2022)
Virtual education plays a very important role in the teaching and learning process of students; since, it allows the autonomy of the students, they generate flexible environments, greater scope in addition to the adaptability to a new and innovative educational methodology. For this reason, the main objective of this research work is to determine the influence of virtual classes on the learning of 4th year EGB students from the Lucila Godoy School, San Luis de Zapotal. Windows 2022. The methodology of this study has a qualitative approach, since qualitative techniques are used; while the types of research used were descriptive, documentary and field. The type of method used was inductive because the particular premises that served as the basis for the development of general conclusions were analyzed. It is important to mention that to obtain significant data for the investigative process, two techniques were used; the first was a survey applied to 9 4th year students, and the second was an interview applied to two teachers who work in the educational unit under analysis. The results obtained were that virtual classes do influence the learning process, since certain weaknesses that condition the learning process in a significant way were evidenced. Therefore, it is concluded that the contribution generated by virtual classes in learning is minimal; since the environment where this process takes place is not the most suitable for its development.